Relative Roles of Grammar Knowledge and Vocabulary in the Reading Comprehension of EFL Elementary-School Learners: Direct, Mediating, and Form/Meaning-Distinct Effects - Hu, Tsui-Chun; Sung, Yao-Ting; Liang, Hsing-Huang; Chang, Tsung-Jen; Chou, Yeh-Tai (Frontiers in Psychology, 2022)
Despite the recognized importance of grammar knowledge to the reading comprehension of EFL learners, research findings on the relationships among grammar knowledge, vocabulary, and reading comprehension are inconclusive. Attention needs to be paid to issues such as the distinct roles of the two grammar knowledge components of form and meaning, and the direct and mediating roles of vocabulary in EFL reading comprehension. This study recruited 1,149 sixth graders as research participants to evaluate these issues. The measurement tools were standardized EFL competence tests for vocabulary size, grammar forms and meanings, and reading comprehension. Structural equation modeling (SEM) regression models indicated that vocabulary played a more-significant role in reading comprehension than grammar knowledge; moreover, the effects of grammar knowledge were reduced but still significant when grammar meanings were excluded. The SEM mediating model of this study also indicated that grammar knowledge not only exerted a direct effect on reading comprehension but also indirectly influenced reading comprehension via vocabulary.